Evaluating the Long-Term Effects of Prisoner Reentry Services on Recidivism: What Types of Services Matter?. (2nd January 2017) - Visher, Christy A.; Lattimore, Pamela K.; Barrick, Kelle; Tueller, Stephen
Abstract : We analyzed data collected for a large multi-site evaluation of 12 prisoner reentry programs in 12 states to examine the impact of pre-release services on time to rearrest and number of rearrests up to 56 months post-release for male offenders. A two-stage matching quasi-experimental design was used to define the comparison groups and multivariate models were used to examine the relationships among service and program receipt and recidivism. Participation in the reentry program was associated with longer time to arrest and fewer arrests after release. However, the specific services delivered as part of the program showed modest or inconsistent impacts on recidivism. Services that focused on individual change were more beneficial than services that focused on practical skills and needs. Practitioners should consider careful sequencing of program and service delivery in prison, linking in-prison services to post-release assistance, and evaluating all services and programs for fidelity and effectiveness.